Evolution of Interferons and Interferon Receptors - Secombes, Chris J.; Zou, Jun (Frontiers in Immunology, 2017)
The earliest jawed vertebrates (Gnathostomes) would likely have had interferon (IFN) genes, since they are present in extant cartilaginous fish (sharks and rays) and bony fish (lobe-finned and ray-finned fish, the latter consisting of the chondrostei, holostei and teleostei), as well as in tetrapods. They are thought to have evolved from a class II helical cytokine ancestor, along with the interleukin (IL) -10 cytokine family. The two rounds (2R) of whole genome duplication (WGD) that occurred between invertebrates and vertebrates (Nakatani et al., 2007) may have given rise to additional loci, initially containing an IL-10 ancestor and IFN ancestor, that have duplicated further to give rise to the two loci containing the IL-10 family genes, and potentially the IFN type I and IFN type III loci (Siupka et al., 2014). The timing of the divergence of the IFN type II gene from the IL-10 family genes is not clear but was also an early event in vertebrate evolution. Further WGD events at the base of the teleost fish, and in particular teleost lineages (cyprinids, salmonids) have duplicated the loci further, giving rise to additional IFN genes, with tandem gene duplication within a locus a common occurrence. Finally, retrotransposition events have occurred in different vertebrate lineages giving rise to further IFN loci, with large expansions of genes at these loci in some cases. This review will initially explore the likely IFN system present in the earliest Gnathostomes by comparison of the known cartilaginous fish genes with those present in mammals, and will then explore the changes that have occurred in gene number/diversification, gene organisation, and the encoded proteins during vertebrate evolution.